JAPANS’S CHINA STRATEGY - A. A. Kireeva (Vestnik MGIMO-Universiteta)
The article deals with the transformation of Japan’s strategy vis-a-vis China. China and Japan are the most powerful states in East Asia in economic, political and military dimensions. They constitute two poles which shape the regional subsystem of international relations. China’s rise presents a considerable challenge for Japan’s foreign policy alongside with immense opportunity for the state’s development, with Japan’s and China’s positions, as well stability in East Asia resting upon Japan’s strategy towards China. Japan’s China strategy in the aftermath of World War II prior to 2010-2011 can be characterized as engagement with elements of containment. Japan has to a significant degree accommodated China’s rise by facilitating the successful implementation of its grand strategy, seen as the restoration of a great power status that China lost in the 19th century opium wars. The beginning of the 21st century saw a reassessment of Japan’s foreign policy and adopting a proactive stance. There is a divergence of opinion as to Japan’s strategy towards China in 2000s: while a number of scholars believe that there was a shift to balancing, others conclude that no such trend existed and “hedging” would be a more accurate definition, as it enables a state to protect from risks with regional coalitions. The early 2010s have seen Japan’s China strategy increasingly transforming into balancing and containment influenced by Japan’s growing perception of China’s maritime activities in the East China Sea as a threat to its security. However, there is growing possibility of adopting a “dual hedging” strategy, as China is first of all regarded as the key economic partner for Japan’s successful development.